Juvenile morphology of the ornamental crab Mithraculus forceps A. Milne-Edwards, 1875 (Crustacea, Brachyura) - Galiotti, Lucas Lopes [UNESP]; Antunes, Mariana [UNESP]; Bolla, Eduardo A. [UNESP]; Negreiros-Fransozo, Maria Lucia [UNESP] (Magnolia Press, 2022)
The morphology of juveniles of Mithraculus forceps A. Milne-Edwards, 1875, raised in the laboratory, is described. The larvae were obtained from ovigerous females collected in the wild, maintained in the rearing system for culture of crabs (400 L). A total of 229 larvae (zoea I), from 7 females were distributed in lots of 20 larvae kept in glass flasks (500 ml), with seawater circulation and temperature and salinity constants, which were checked daily for molts or deaths. After the larvae reached the juvenile stage, exuviae and dead specimens were deposited in a scientific collection. We analyzed the external morphology (N = 10 ind.) of each size class (total = 8). We determined the number of size classes, based on carapace width CW vs. carapace length CL (mm) and its dispersion points, in which we can observe non-hierarchical groupings with no size classes overlapping. We analyzed the relative growth of the juveniles using the technique “Standard Major Axis’’ (Type II regression). The relationships CW vs. CL and CW vs. AW showed negative allometry (b < 1; p < 0.05). The relationships CW vs. CPH and CW vs. CPL are isometric (b = 1; p > 0.05). The most remarkable morphological characters of the juveniles (first size class) are the following: spines at the anterior margin of the carapace, inner marginal teeth in the propodus and dactylus of the chelipeds, number of articles in the antennular endopod and the maxillular endopod, absence of setae on the maxillar endopod, and absence of rudimentary pleopods.
Keywords: crabs; culture; development; juveniles; Mithracidae